IMPROVING STUDENTS VOCABULARY ACHIEVEMENT THROUGH WORD WALLS STRATEGY AT EIGHT GRADE OF MTs HIFZI LQUR’AN MEDAN - Muifda Nst, Layla (BRIGHT VISION Journal of Language and Education, 2021)
This research was conducted to describe the improvement of students’ vocabulary achievement through word walls strategy at eight grade of Mts Hifzil Quran Medan in 2020/2021 academic year. The research design used was Classroom Action Research (CAR).. The subject of the research was VIII-1 class MTs Hifzil Qur’an Medan which consisted of 25 students. The research was conducted in two cycles and each cycle consisted of three meetings. The results showed that the improvement of the students’ scores from the first test in orientation test to the third test in cycle-II test. In the first orientation test, the mean was 48.48, in the second test in cycle-I test, the mean was 63.68, and the third test in cycle-II test, it was improved to be 79.04. Based on the diary notes, observation sheet, and questionnaire, it was found that the teaching learning activities ran well. Students were active and enthusiastic during the teaching learning process in second cycle than the first one. The result of the researcher showed that the use of word walls strategy significantly improved students’vocabulary